2014
DOI: 10.1088/1748-9326/9/2/024001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of engineered cobalt, iron, nickel and silver nanoparticles on soil bacterial diversity under field conditions

Abstract: Our understanding of how engineered nanoparticles (NPs) migrate through soil and affect microbial communities is scarce. In the current study we examined how metal NPs, including those from the iron triad (iron, cobalt and nickel), moved through pots of soil maintained under winter field conditions for 50 days, when mesophilic bacteria may not be dividing. Based on total metal analysis, cobalt and nickel were localized in the top layer of soil, even after exposure to high precipitation and freeze-thaw cycles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…Lysobacter (Chen, Shi, & Wang, 2012;Puopolo et al, 2016;Shah, Collins, Walker, & Shah, 2014). In addition, the data analysis identified that the bacterial genus Bacillus was positively related to the increased levels of the heavy metals in the soil.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lysobacter (Chen, Shi, & Wang, 2012;Puopolo et al, 2016;Shah, Collins, Walker, & Shah, 2014). In addition, the data analysis identified that the bacterial genus Bacillus was positively related to the increased levels of the heavy metals in the soil.…”
Section: Discussionmentioning
confidence: 93%
“…The above findings imply that in the case of the metal contaminated paddy soils, the bacterial species, more sensitive to the heavy metals and lacking metal resistance mechanisms, are replaced by the more tolerant species. The applied data analysis approach also enabled the identification of bacterial taxa that contributed to the observed differences among the studied bacterial communities most significantly and included the metal‐tolerant genera such as Arenimonas , Ferruginibacter , Flavobacterium , and Lysobacter (Chen, Shi, & Wang, ; Puopolo et al., ; Shah, Collins, Walker, & Shah, ). In addition, the data analysis identified that the bacterial genus Bacillus was positively related to the increased levels of the heavy metals in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…For example, iron oxide nanoparticles (Fe 2 O 3 NPs) have been used extensively in many fields including microelectronics, biomedical imaging, and the detection and visualization of various phases and interfaces in oil reservoirs (Basnet et al 2013;Laurent et al 2008;Mahmoudi et al 2011). The increased prevalence of engineered nanoparticles (ENPs) has led to their release into the environment, which is potentially having an impact in living organisms (Shah et al 2014;Zhao et al 2014), especially plants Liao et al 2014;Martinez-Ballesta and Carvajal 2014). How these NPs may affect food safety and quality is of particular concern.…”
Section: Introductionmentioning
confidence: 99%
“…Based on findings of such studies it has been anticipated that the denitrifying bacterial community is assumed to be highly susceptible to nanoparticles toxicity (Throbäck et al, 2007; VandeVoort and Arai, 2012). Despite the clearly known impact of nanoparticles on soil microbial community, there exists a dearth of literature providing apparent connection between soil factors and toxic behavior of nanoparticles toward soil biota (Calder et al, 2012; Chunjaturas et al, 2014; Shah et al, 2014; Mishra and Singh, 2015a). In this context, Frenk et al (2013) evidenced effect of copper oxide (CuO) and magnetite (Fe 3 O 4 ) nanoparticles on soil bacterial community in two different soil types (sandy loam and sandy clay loam).…”
Section: Concerning Risk Assessment Factors and Their Modulation For mentioning
confidence: 99%